Differentiation in Protest Politics: Participation by Political Insiders and Outsiders - Endre Borbáth (Political Behavior, 2024)
The political participation literature has documented a long-term trend of the normalization of noninstitutional participation that is often equated with the conventionalization of engagement in protest politics. Less is known on the extent to which noninstitutional forms are differentiated by their mobilization context. Population surveys find it difficult to contextualize individual engagement, and on-site surveys point to effects that are hard to generalize. This study fills this gap by emphasizing differentiation and distinguishing participation according to the issue of engagement. It introduces a conceptual distinction between political insiders and outsiders, defined based on the extent to which they are embedded in the organizational landscape of the dominant cleavage dimension. Using an original survey conducted in Germany during the Covid-19 crisis, the analysis demonstrates that general-population surveys are fit to examine issue-specific participation patterns. The results expose an insider and outsider divide, captured by the effect of attitudinal and behavioral indicators, and demonstrates that the two groups are equally likely to participate in noninstitutional forms. However, insiders engage on the established issues of climate and anti-racism, whereas outsiders engage on the new issues of Covid-19 related economic assistance and civil liberties restrictions. In addition, dynamic models reveal that noninstitutional participation is rooted in volatile issue preferences. Overall, the paper argues that participation during the Covid-19 crisis has furthered the trend towards a differentiated protest arena.
doi:10.7910/DVN/IBZAOJ
Keywords: 320; Political participation; Covid-19; Protest; Germany; Political issues; Surveys